Nanoenabled Photothermal Materials for Clean Water Production - Irshad, Muhammad Sultan; Arshad, Naila; Wang, Xianbao (Global challenges, 2021)
Solar‐powered water evaporation is a primitive technology but interest has revived in the last five years due to the use of nanoenabled photothermal absorbers. The cutting‐edge nanoenabled photothermal materials can exploit a full spectrum of solar radiation with exceptionally high photothermal conversion efficiency. Additionally, photothermal design through heat management and the hierarchy of smooth water‐flow channels have evolved in parallel. Indeed, the integration of all desirable functions into one photothermal layer remains an essential challenge for an effective yield of clean water in remote‐sensing areas. Some nanoenabled photothermal prototypes equipped with unprecedented water evaporation rates have been reported recently for clean water production. Many barriers and difficulties remain, despite the latest scientific and practical implementation developments. This Review seeks to inspire nanoenvironmental research communities to drive onward toward real‐time solar‐driven clean water production. Nanoenabled photothermal materials and their respective photothermal mechanisms, surface plasmon resonance, non‐radiative relaxation, and lattice vibrations are briefly described. The entire solar‐driven steam generation process, liquid to vapor generation, and vapor condensation along with a theoretical understanding of evaporation rate limitations is discussed. The bifunctional water‐energy nexus is reviewed for simultaneous water and electricity generation. In addition, the decisive challenges of this field are put forward.